KOMPARASI UU NO. 1 TAHUN 2015 DENGAN UU NO. 14 TAHUN 2015 TENTANG PEMILIHAN KEPALA DAERAH SATU PASANGAN CALON DITINJAU DARI FIQH SIYASAH - DEWI SIREGAR, HARIATI NOVRINA (Institut Agama Islam Negeri Padangsidimpuan, 2017)
Regional head elections are those given by the central government to run the government in the region. The regional head in the context of Indonesia is the governor and deputy governor, regent and deputy regent, and mayor and deputy mayor. Since 2005, regional heads and deputy regional heads have been elected through the people directly through general elections. This research focused to reveal how the regulation and mechanism of regional head elections for one candidate pair. This research uses library research through qualitative approach that is research that intends to interpret the phenomenon of what is experienced by the subject of research. The data were obtained from primary and secondary data, while the technique of data collection was done by collecting primary and secondary materials related to regional head elections with one candidate pair. The technique of analysis data was done by using normative research through comparative analysis or analysis of differences. The results of the research indicated that the comparison between UU No. 1 of 2015 with UU No. 14 of 2015 concerning regional head elections has a side of equality. It can be seen from the process, implementation, voter, and the most votes. However, the difference between UU No. 1 of 2015 existence of a candidate pair must be followed by the conditions of two candidate pairs, but in UU No. 14 of 2015 is permitted the existence of one pair of candidates with certain conditions. If viewed from the fiqh siyasah for the election of regional heads, one pair of candidates, in siyasah fiqh is allowed and legitimate the existence of one candidate pair.